The Effect of Methyltestosterone Hormone Immersion on Male Formation in Gourami Larvae (Osphronemus goramy Lacepè¨de, 1801) - Tatang, Tatang; Sriwidodo, Maheno; Riniwati, Harsuko (Graduate School, Universitas Brawijaya, 2020)
The methyltestosterone hormone is a synthetic hormone of androgen and has been used to obtain the juveniles of male mono-sexual fish such as Tetra Congo, Tilapia, and Betta. The methyltestosterone use on gourami has not maximized. It because there is no data on the exact age of larvae to produce maximum male mono-sexual juveniles, so it is necessary to do research on the effect of methyltestosterone hormone on the age of gourami larvae on the success of male mono-sexual formation and get the right larval period to obtain maximum survival gourami. The methods of this research were conducted using a completely randomized design with four treatments of the age of gourami larvae aged ten days, 15 days, 20 days, and 25 days. Each procedure was repeated three times. Data analysis used ANOVA analysis and LSD test. The larvae are soaked in a solution containing 5 ppm of hormones for 24 hours. The results showed that the administration of the hormone methyltestosterone to gourami larvae (Osphronemus goramy Lacepè¨de, 1801) with different ages had a very significant effect (P <0.01) on male sex formation with the highest average percentage of males obtained in treatment B (15-day larvae age) that is equal to 82.33% and the lowest in the treatment of larval period of 10 and 20 days is 74.00%. Keywords: Gourami, hormone, juvenile, methyltestosterone, Osphronemus goramy.